In desmoid-type fibromatosis cells sorafenib induces ferroptosis and apoptosis, which are enhanced by autophagy inhibition. Issue 7 (July 2022) - Schut, Anne-Rose W.; Vriends, Anne L.M.; Sacchetti, Andrea; Timbergen, Milea J.M.; Alman, Benjamin A.; Al-Jazrawe, Mushriq; Grünhagen, Dirk J.; Verhoef, Cornelis; Sleijfer, Stefan; Wiemer, Erik A.C.
Abstract: Introduction: Desmoid-type fibromatosis (DTF) is a rare, soft tissue tumour. Sorafenib, a multikinase inhibitor, has demonstrated antitumour efficacy in DTF patients. Little is known about the underlying molecular mechanisms, which are crucial to know to further optimize systemic treatments. Here we investigated the molecular effects of sorafenib exposure on DTF and stromal cells, with an emphasis on cell death mechanisms. Material and methods: DTF primary cell cultures, with known CTNNB1 status, and primary stromal cell cultures, derived from DTF tissue, were exposed to clinically relevant concentrations of sorafenib in the presence or absence of inhibitors of ferroptosis, apoptosis and autophagy. Cell viability was determined after 24 and 48 h using MTT assays. Annexin V/PI staining, lipid peroxidation analysis and immunoblotting were performed to assess apoptosis, ferroptosis and autophagy. Results: Exposure to sorafenib caused a significant, concentration- and time-dependent decrease in cell viability in all primary DTF and stromal cell cultures. Inhibitors of ferroptosis and apoptosis protected against sorafenib-mediated cytotoxicity implicating that both cell death mechanisms are activated. Annexin V/PI stainings and lipid peroxidation analyses confirmed induction of apoptosis and ferroptosis, respectively. Autophagy inhibition enhanced the cytotoxic effect of sorafenib and led to a stronger induction of apoptosis and ferroptosis. Conclusion: This study identified ferroptosis and apoptosis as mechanisms for the sorafenib induced cell death in DTF cells as well as stromal cells. Furthermore, autophagy inhibition enhanced the cytotoxic effects of sorafenib. Knowledge of the mechanisms by which sorafenib affects DTF at a cellular level may help to optimize its clinical efficacy and mitigate toxic effects.